Pengaruh Gaya Hidup dan Self Efficacy terhadap Fear Of Missing Out (FOMO) pada Pegawai CV. Sarana Karya Mandiri - Insania Aulia Nursidqiyah (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
The phenomenon of fear of missing out (FoMO) has become a major concern, especially among generation z. There is a gap between lifestyle factors and self-efficacy regarding what understanding and contribution affects it. This study aims to find out whether there is an influence between lifestyle and self efficacy on FoMO. The population of this study is 40 CV employees. Sarana Karya Mandiri by using the total sampling method. Data analysis consists of descriptive and inferential analysis. The results of the study showed that the average respondents' answers were on a scale of disagreement. There is a significant influence between lifestyles on FoMO. There is a significant influence between self-efficacy and FoMO. There is a significant influence between lifestyle variables and self efficacy together on FoMO. CV Employee. Sarana Karya Mandiri should be able to control itself from trends and social media and be able to distinguish various positive and negative things provided by social media. Companies can provide education about lifestyle, self-efficacy or self-confidence and matters related to FoMO.